Implementation of the Quality Function Deployment (QFD) Method to Redesign a Walker for the Elderly - Ribangun Bamban Jakaria; Evina Dewi Lestari; Iswanto; Nur Haizal Binti Mat Yaakop @Arifin; Marzuki Bin Ibrahim (Universitas Muhammadiyah Sidoarjo, 2023)
The walker is a very light and easy to move, waist-high, walker made of metal tubing and this tools is equipped with two algae that function as a place for its use to hold on and is equipped with four sturdy legs as a support. This study aims to obtain an ergonomic walker design and provide a level of satisfaction to customers. To redesign the walker, the Quality Fuction Deployment (QFD) method is used because it can be used for product development of walker design, meeting customer needs and desires.The result obtained in this study are the redesign of the walker to increase customer satisfaction by using the quality function deployment (QFD) method with four phases which are implemented into the House Of Quality (HOQ). The result of the walker product design have a value of normalized raw weight above 10% consisting of 16 attributes, namely has features as a seat 7,897%, the product has a simple, comfortable and foldable shape 7,280%, the product is comfortable to sit and lean on 7,573%, speed in customer service for repair 7,776%, the resulting product is a product with high quality 7,806%, the resulting product has a positive impression in terms of design and attached accessories 7,503%, the product has a technical age of approximately 10 year 7,513%. This is because this attribute is very important, based on the desired characteristics of walker user from a product.